Diploid potato germplasm derived from wild and landrace genetic resources - Watanabe, K.; Orillo, M.; Iwanaga, Masaru; Ortíz, R.; Freyre, R.; Pérez, S. (1994)
Diploid cultivated species, haploids derived from tetraploid cultivars, and their wildSolanum relatives were used to generate various diploid potato genetic stocks. These stocks have significant value in potato breeding because: 1) genetic diversity in the potato population can be kept variable with the diploid germplasm which confers genetic variation from wild and cultivated species; 2) crossability of this diploid germplasm is facilitated by the function of 2n gametes; and 3) high levels of pest resistances originating from the process of introgression of the wild and cultivated genetic resources can be used to improve the tetraploid cultivated potato genepool.